Turismo rural e sustentabilidade : o caso de municípios do Espírito Santo - Santos, Telma Mara Bittencourt Bassetti (2009)
The main objective of this dissertation is to relate the touristic activity in rural areas of some municipalities in the State of Espírito Santo to the life standing of their residents, having the local tourism as a perspective. In order to evaluate the life conditions in the selected municipal districts we have chosen the Municipal Human Development Index (MHDI) that will be the starting point to hierarchize the municipal districts as well as to compare the population s improvement evolution life conditions, in those aspects, among the years 1991 and 2000. In the same way, the population growth IBGE data from the years 1991 to 2000 will be used. This datum will be related to the 2003 tourist flow one which will be provided by the Tourism Clerkships. Afterwards, these data will be related to some public services offer (water supply, sewage system and garbage disposal) among the years 1991 and 2000. The 2000 Espírito Santo Municipal Development Index (ES-MDI) and the 2001 municipal tributary revenues will also be used to hierarchize them. Another objective is to evaluate the participation of the public policies in tourism development in those chosen municipalities, taking as an example the Tourism Municipality National Plan (TMNP) from the analysis of the Implementation Program Reports and some contacts with the Brazilian tourism Institute (EMBRATUR) and TMNP Executive Secretary in Espírito Santo. The chosen municipalities for this dissertation. (Afonso Cláudio, Domingos Martins, Marechal Floriano and Venda Nova do Imigrante) are situated in a mountainous micro-region in the State of Espírito Santo. We arrived the conclusion that although it can have improvements in the life conditions starting from the tourism, the tourist activity needs to be accompanied of improvement in the infrastructure services for not committing the sustainable of the life conditions in the municipal districts.